Dualism, mixedness and cross-breeding in legal systems: Quebec and Canadian law - Morin, Michel (2018)
This paper will introduce the reader to one mixed system, that of Quebec. It will begin by reviewing briefly the differences between legal systems and legal traditions (section 2). Next, it will explain how the law of Quebec is derived from a variety of French and English rules, and ask to what extent these mixed sources had rendered its civil law and its common law culture qualitatively different from their European models, that it too say, hybrid (section 3). It will then discuss how Canadian law accommodates various legal orders such as the civil law and Indigenous legal traditions (section 4).